Philosophy of Theatre. A Methodological Perspective - Ceraolo, Francesco (Filosofia, 2021)
Ancient practice long ignored by theatre studies, philosophy of theatre has recently resurfaced. While from Aristotle onwards it has traditionally represented a speculative analysis on the nature of the theatrical object, philosophy of theatre is now becoming a proper methodology that allows to place the truth-bearing value of theatrical practice at the centre of reflection. The philosophical approach to the theatre aims to evaluate the theatrical object or practice (a show, a document, a theory, and so on) revealing the way in which its generically expressive effect is capable of broadening meaning, in the evolution of both the forms intrinsic to the language and those that are generically human. The philosophical approach ultimately is a methodology that allows to re-establish – in critical and reflective practices – the crucial connection between theatre and life, beyond any evaluative and descriptive practice of the object of analysis. Starting from a series of examples of philosophical reflections (Lukács, Badiou, Puchner, Sini, Rokem), this paper aims to show how such a methodology might still open up productive areas of research on theatre in the present day. Finally, the need for a new philosophical reflection on the theatre in the aftermath of the Covid-19 pandemic will be examined, with particular reference to the concept of presence and its crucial relation to mediation practices.